Loperamide poisoning resulting in death: a case report and literature review - Wang, Bowen; Zhang, Zhan; Chen, Ke; Du, Zhongyang; Zhang, Tianchen; Xie, Ping (Frontiers in Pharmacology, 2025)
Loperamide is a medication commonly used to treat acute and chronic diarrhea and is generally considered safe because it poorly crosses the blood-brain barrier at therapeutic doses. However, in recent years, with the abuse and overdose of loperamide, its potential cardiotoxicity and central nervous system depression have increasingly raised concerns. This article reports a case of a 15-year-old male patient who died from poisoning after a single ingestion of 60 mg of loperamide. The patient took a large dose of loperamide 6 h before admission and was found to have respiratory and cardiac arrest 1 h before admission. Despite cardiopulmonary resuscitation and advanced life support treatment, the patient ultimately died from irreversible brain damage. Electrocardiography showed significant QTc interval prolongation, and the plasma loperamide concentration was 50 ng/mL, indicating loperamide’s cardiotoxicity. This article, through this case and a review of the literature, discusses the mechanisms of loperamide’s cardiotoxicity, clinical manifestations, and treatment strategies, aiming to enhance clinicians' awareness of loperamide poisoning.